A New Concept of Work Engagement Theory in Cognitive Engagement, Emotional Engagement, and Physical Engagement - Huang, Stanley Y. B.; Huang, Chien-Hsiang; Chang, Tai-Wei (Frontiers in Psychology, 2022)
The concept of work engagement (WE) has aroused the interest of many scholars. However, there has been limited academic research in examining how authentic leadership (AL) can influence increases in WE, which consequently influences the increases in the organizational citizenship behavior (OCB) and task performance (TP). In particular, this study divides WE into cognitive engagement, emotional engagement, and physical engagement to fully reflect Kahn’s (1990) engagement theory. This study used the modeling of latent growth curve to survey the three dimensions of WE, including its antecedents (AL) and consequences (OCB and TP), and tested the theoretical model using a longitudinal study in six months to confirm the validity of cognitive engagement, emotional engagement, and physical engagement. Empirical testing using a survey of 251 employees of retail travel agencies in Taiwan revealed that the AL can influence the increase in the three dimensions of WE and then influence the increases in the OCB and TP. These analysis results can assist vendors to implement OCB and TP through WE and AL.